Deep Incarnation God's Redemptive Suffering with Creatures - Edwards, Denis (Orbis Books, 2019)
"Based on the Duffy Lectures, a yearly lecture series at Boston College, this book explores the theme of "Deep Incarnation" as a way of making connections between incarnation and the whole of creation, including the costs built into our evolutionary world. The key question of "Deep Incarnation," for Edwards, is: "What relationship is there between the wider natural world, the world of galaxies and stars, mountains and seas, bacteria, plants and animals, and the life, death, and resurrection of Jesus Christ?" To approach this theme, Edwards draws upon the work of Niels Gregersen (the "father of Deep Incarnation"), Elizabeth Johnson, and others. He then engages with Irenaeus, Athanius, and Karl Rahner as three great witnesses to a deep view of incarnation, and concludes with his own constructive approach to the book's theme."